Obstetric Outcomes after Cervical Cerclage in Women with Cervical Insufficiency: Cervical Cerclage with Cervical Insufficiency - Bilal, Mahjabeena; Rashid, Uzma; Shakeel, Asma; Habib, Mahnoor; Sara, .; Yousaf, Sabrina (Pakistan Journal of Health Sciences, 2025)
Most of the local studies in Pakistan have focused only on the prevention of preterm labour after cervical cerclage in women with cervical insufficiency. Still, these studies lack data regarding other outcomes like abortion and premature rupture of membranes after cervical cerclage in women with cervical insufficiency. Objective: To determine the obstetric outcomes after cervical cerclage in women with cervical insufficiency. Methods: This descriptive study was carried out at the Gynaecology Department, Khyber Teaching Hospital, during the period 22nd May 2024 till 31st March 2025. Women aged 18-35 years with gestational age 13 to 20 weeks and transvaginal ultrasound showing cervical length <2.5cm were enrolled. Cervical cerclage was performed, and pregnancy outcomes were noted in terms of miscarriage, preterm, PROM, prolonged pregnancy and term pregnancy. Results: Mean age of the participants was 30.42 ± 5.616 years, mean BMI was 24.070 ± 2.704kg/m2 and mean gestational age was 24.37 ± 4.844 weeks. 85 patients (50.3%) were aged more than 30 years. Participants with parity up to 3 were 94 (55.6%), and 126 patients (74.6%) were housewives. Preterm was the most common pregnancy outcome, recorded in 58 patients (34.3%), 34 patients (20.1%) had a term pregnancy, and prolonged labor was the least common (n=8, 4.7%). Conclusions: Preterm delivery was the most common pregnancy outcome after cervical cerclage in this cohort of patients. However, a reasonable number of patients were found with a term pregnancy, showing the adequate prolongation of pregnancy with cerclage in cervical insufficiency.